2019
DOI: 10.1016/j.schres.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Simulated car driving and its association with cognitive abilities in patients with schizophrenia

Abstract: It is concluded that driving of patients with schizophrenia is characterized by a relatively slow speed, and can also be impaired in certain aspects, i.e. hindering a car behind while merging. Cognitive functions are crucial for driving, and should be target of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Overall, with regard to antipsychotic medication, a great proportion of schizophrenic and schizoaffective patients does not reach the level of psychomotor or driving simulator performance of healthy controls following long-term treatment despite significant clinical improvement ( Wylie et al, 1993 ; Soyka et al, 2005 ; Fuermaier et al, 2019 ). Keeping in mind the great heterogeneity between studies, on average 31% (27%–42.5%) of in-patients showed severe impairment of psychomotor function relevant for driving under steady-state pharmacological conditions prior to hospital discharge; that is, patients were treated in most cases 6 weeks and more in a stationary setting ( Brunnauer et al, 2004 , 2005 , 2009 , 2012 ; Soyka et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, with regard to antipsychotic medication, a great proportion of schizophrenic and schizoaffective patients does not reach the level of psychomotor or driving simulator performance of healthy controls following long-term treatment despite significant clinical improvement ( Wylie et al, 1993 ; Soyka et al, 2005 ; Fuermaier et al, 2019 ). Keeping in mind the great heterogeneity between studies, on average 31% (27%–42.5%) of in-patients showed severe impairment of psychomotor function relevant for driving under steady-state pharmacological conditions prior to hospital discharge; that is, patients were treated in most cases 6 weeks and more in a stationary setting ( Brunnauer et al, 2004 , 2005 , 2009 , 2012 ; Soyka et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…While polydrug treatment is frequent in clinical practice, only a few studies could be identified that investigated driving performance under common psychopharmacologic treatment combinations in schizophrenic or schizoaffective patients. Irrespective of drug regimen, most patients do not seem to reach the level of psychomotor or driving simulator performance of healthy controls following subchronic or long-term polydrug treatment and psychopathologic stabilization ( Hobi et al, 1981 ; Grübel-Mathyl, 1987 ; Wylie et al, 1993 ; Soyka et al, 2005 ; Fuermaier et al, 2019 ). In clinical routine settings, where patients were co-medicated with lithium, valproate, hypnotics, or antidepressants in addition to treatment with SGAs or FGAs, 32%–54% of patients showed a very low test performance in functional domains relevant for driving, with a better performance of patients under polydrug treatment with SGAs ( Grabe et al, 1999 ; Kagerer et al, 2003 ).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…Second, a greater CV of the inter‐vehicle distance in the car‐following task may be not always indicate impaired driving performance; it may imply that patients with BD tried to maintain sufficient inter‐vehicle distance as good compensatory behavior. The possibility of good compensatory driving behavior has been reported in patients with schizophrenia 39 . Meanwhile, the road‐tracking task is a monotonous scenario used as standard when evaluating the effects of psychotropic drugs on driving performance, and is susceptible to impaired attention and drowsiness 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 1 of attention deficit of people with schizophrenia found that it mainly affects sustained attention and recommended further investigation into sustained attention of relation to people with schizophrenia (Hoonakker et al, 2017). Another report on the driving ability of patients with schizophrenia found that they tend to drive abnormally slow and have poor driver reaction time (Fuermaier et al, 2018). A study involving 98 outpatients with schizophrenia found that their performance in reaction time was strongly correlated with their performance in emotional cognitive function (Lahera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another scholar indicated that people with schizophrenia tend to experience declining sustained attention with age (Hoonakker et al, 2017). Although human attention function has various facets, new research literature has identified attention deficit among schizophrenic patients from reaction times and sustained attention (Fuermaier et al, 2018;Hoonakker et al, 2017;Sepede et al, 2014). Accordingly, psychiatric occupational therapy should focus on the attention assessment methods for these two aspects.…”
Section: Introductionmentioning
confidence: 99%